First-person Narrative in the Performative Practice of Marginalized Women and Decolonial Knowledge Production - Silva, Caroline Dias de Oliveira (Revista Brasileira de Estudos da Presença, 2021)
First-Person Narrative in the Performative Practice of Marginalized Women and Decolonial Knowledge Production – The essay proposes a dialogue between feminist decolonial thinking and performance art, as they connect to my own experience in these fields. Based on the understanding that the decolonial perspective puts all Western conceptual and methodological categorizations under critical scrutiny, my objective is to advance discussion of performance by marginalized women, seeking to understand their role in the production of shared meanings through disruptive and anti-colonial writing. To this end, I examine performative actions that deploy such practices, which I understand as initiatives toward decolonization through embodied expression